Development of Executive Functions: Implications for Educational Policy and Practice. (October 2016) - Serpell, Zewelanji N.; Esposito, Alena G.
Executive functions refer to top–down processes utilized in goal-directed behavior. Executive functions and academic achievement relate robustly, from early childhood through adolescence. Executive functions and their neural networks appear to be malleable, and environments can support their development. Varied approaches, including educational curricula, structured physical exercise, and computer-based training, can improve executive functions. The intervention work suggests that children who are most "at-risk" demonstrate the largest gains, but evidence of far transfer to academic achievement or other behavioral outcomes that are important to schools is at this point only promising. The review highlights developmental considerations for measurement and intervention, and discusses implications for schools in supporting children's development of executive functions. Policy implications of the scientific findings suggest strategies for providing environments that foster the development of executive functions.